2005
DOI: 10.1590/s1413-86702005000600006
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the residual risk for the transmission of HIV in blood donors from the mountain region of Santa Catarina

Abstract: The HIV, in hemotheraphy, may be transmitted by erythrocyte, platelets, crioprecipitated, frozen fresh plasma and possibly, by other blood components. Appropriate legislations for this new reality were elaborated normatizing the hemotheraphy practices in Brazil, creating a set of procedures and actions aiming at guaranteeing the quality of the blood, during the whole process. However, the residual risk remains, and it can be calculated as a product of the incidence and period of the immunological window. The o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The quantifi cation of residual risk is an important part of blood safety policies worldwide 2 . In Brazil, the methodology of residual risk estimation had been disseminated in the Portuguese language by the end of the 1990s 3,4 and has been sporadically applied in the country since then 1,[5][6][7][8][9][10] . The results of these studies showed high prevalence, incidence and residual risk in Brazil compared with the United States of America (USA), Europe, Japan and Australia, thus reinforcing the need to monitor these parameters in a systematic way and to use them to evaluate the effectiveness of transfusion safety measures.…”
mentioning
confidence: 99%
“…The quantifi cation of residual risk is an important part of blood safety policies worldwide 2 . In Brazil, the methodology of residual risk estimation had been disseminated in the Portuguese language by the end of the 1990s 3,4 and has been sporadically applied in the country since then 1,[5][6][7][8][9][10] . The results of these studies showed high prevalence, incidence and residual risk in Brazil compared with the United States of America (USA), Europe, Japan and Australia, thus reinforcing the need to monitor these parameters in a systematic way and to use them to evaluate the effectiveness of transfusion safety measures.…”
mentioning
confidence: 99%
“…In the first half of the decade 2000, Spada et al (2005) found the HIV prevalence in blood donors varying between 0.02% in the Mountain Highland region and 0.04% reported by Kupek (2004) in Florianópolis. Present study indicates a significant reduction of average HIV prevalence in blood donor population to 0.006%, with the range between 0.001% to 0.01%.…”
Section: Resultsmentioning
confidence: 99%